The Relationship between Platelet Aggregation and Time Interval after Venepuncture - Warlow, Charles; Corina, Anne; Ogston, D; Douglas, A. S (Thrombosis and Haemostasis, 1974)
The relationship between the rate of platelet aggregation and the time interval after venepuncture has been studied. Considerable changes in the rates of aggregation and disaggregation of platelets in citrated plasma take place between 30 and 120 minutes after venepuncture. There is a reduction in the rates of irreversible ADP-induced aggregation, the first and second phase of the double wave of ADP-induced aggregation, disaggregation after reversible ADP-induced aggregation, collagen-induced aggregation and the second phase of the double wave of adrenaline-induced aggregation. In contrast, the rate of the first wave of adrenaline-induced aggregation increases with time after venepuncture. 5-HT induced aggregation appears to be unaffected. These effects were not due to changes in the pH of the plasma. It is suggested that any attempt to quantify platelet aggregation during the comparison of groups of individuals, or in the study of the effect of anti-platelet drugs in single individuals must take into account the time interval between venepuncture and the measurement of platelet aggregation.